2015
DOI: 10.1159/000369389
|View full text |Cite
|
Sign up to set email alerts
|

A Giant Ovarian Tumor Causing Anasarca and Dyspnea Successfully Managed after Preoperative Drainage

Abstract: Serious complications are likely to accompany the treatment of giant ovarian tumors, and resection with or without preoperative drainage has been previously reported. Here, we report the case of a 27-year-old Japanese woman with a significant weight gain of 50 kg, who was referred to the Kumamoto University Hospital because of gait impairment and dyspnea. Imaging tests revealed an ovarian tumor, 37 cm in diameter, with two solid components. The patient's condition improved after the removal of 31.5 l tumor flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…When the ovarian mass expands further, it can cause chest compression and subsequent respiratory impairment. In addition, edema or deep venous thrombosis may be formed by suppression of venous perfusion through pressure on the inferior vena cava 7 . The patient in this study also neglected the symptoms of ovarian tumors because of economic problems and insufficient cancer knowledge.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…When the ovarian mass expands further, it can cause chest compression and subsequent respiratory impairment. In addition, edema or deep venous thrombosis may be formed by suppression of venous perfusion through pressure on the inferior vena cava 7 . The patient in this study also neglected the symptoms of ovarian tumors because of economic problems and insufficient cancer knowledge.…”
Section: Discussionmentioning
confidence: 91%
“…The ovary is an organ inside the pelvis. If abnormal ovarian growth in or on the ovaries is left untreated, the ovarian tumor may continue to expand outside the pelvis 7 . Because of her poor financial situation and psychological state, our patient did not have regular physical examinations.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…It has been recommended that tumor be gradually reduced preoperatively to minimize risk of respiratory and circulatory complications, which can be achieved by drainage of the cyst over several hours or sometimes even a few days [7]. A study conducted in Japan concluded that use of a suprapubic catheter for preoperative drainage of the ovarian cyst decreases the risk of intraperitoneal fluid leakage which may facilitate the spread of potentially malignant cells [8].…”
Section: Complicationsmentioning
confidence: 99%